5r-2r+3=7r-r

Simple and best practice solution for 5r-2r+3=7r-r equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5r-2r+3=7r-r equation:


Simplifying
5r + -2r + 3 = 7r + -1r

Reorder the terms:
3 + 5r + -2r = 7r + -1r

Combine like terms: 5r + -2r = 3r
3 + 3r = 7r + -1r

Combine like terms: 7r + -1r = 6r
3 + 3r = 6r

Solving
3 + 3r = 6r

Solving for variable 'r'.

Move all terms containing r to the left, all other terms to the right.

Add '-6r' to each side of the equation.
3 + 3r + -6r = 6r + -6r

Combine like terms: 3r + -6r = -3r
3 + -3r = 6r + -6r

Combine like terms: 6r + -6r = 0
3 + -3r = 0

Add '-3' to each side of the equation.
3 + -3 + -3r = 0 + -3

Combine like terms: 3 + -3 = 0
0 + -3r = 0 + -3
-3r = 0 + -3

Combine like terms: 0 + -3 = -3
-3r = -3

Divide each side by '-3'.
r = 1

Simplifying
r = 1

See similar equations:

| 7x^2-7x-84= | | -2y=10x+16 | | (3x+5)(x+3)=7 | | 6x-y+5=180 | | 7x-248+x+44=180 | | 30-4x=14 | | 5(x-7)=2(2-2x)-3 | | [9(x+5)-16]+[3(x-2)+4]= | | x+8-1/3=90/11 | | 2x^2+8x-192=0 | | 3x+(x*x)=180 | | 0.06(10-x)(100)= | | x^2-5x=x(5+x) | | x^2-5x=x(5x) | | 2x+55=272 | | (4y-7)+(-2y+5)= | | 2/5(x+3)=6 | | 3x+7-8(x+2)=-36 | | N(N-3)=700 | | 23-4x=9 | | 16x^4-54x= | | 9w-28=2 | | 4a-4=4x+4-2x | | 4t^2-16t+7=0 | | x^7+64x^4=0 | | 3y^2+17y-28= | | 6a+a-9=30 | | 7-5a=17 | | 2(4a+3)=8+6(2a-3) | | 8x-32=-8(4-5x) | | 7(3x-4)=59 | | 3x+-4=14 |

Equations solver categories